Computational Intelligence and Soft Computing: Recent Applications - László, Kóczy; Harmati, István A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The delicate balance of resource intensity and efficiency of a solution for a very complex problem raises the issue of how these aspects constitute a symmetrical or asymmetrical system. Computational Intelligence (CI) offers a plethora of efficient tools for the potential and rather good quality solution of highly complex, often mathematically intractable problems. This "toolbox" is one of the best examples for the study of the above mentioned issue, namely, how to find the best balance, how to establish a symmetry of weights or costs in a particular field, for a particular problem. This special issue presents a number of interesting novel applications of CI for the tackling of a wide variety of difficult problems. The Introduction gives a short insight into the symmetry and asymmetry aspect of the topic.